Effect of Coral Reefs on Wave Height Observed by Satellite Altimetry - Usoltseva, Mariia; Passaro, Marcello; Dettmering, Denise (Remote sensing in earth systems sciences (Online), 2025)
Coral reefs, among other benefits, offer a natural sheltering effect for coastal communities by attenuation of incoming waves. Despite the long-standing scientific interest in this subject, there remains a lack of comprehensive studies that assess wave behavior on coral reefs through satellite altimetry. This study investigates the influence of coral reefs on wave heights using a multi-mission along-track satellite altimetry dataset. Significant wave height statistics for different sea states derived from altimetry are compared with those from the ERA5 reanalysis dataset. Additionally, the role of coral reef structural complexity in wave attenuation is analyzed through regional assessments of altimetry data during calm periods and following destructive storms. The results show a strong agreement between the wave height attenuation observed from satellite altimetry and ERA5 datasets, with a correlation coefficient of 0.724. In 80% of the observations, a significant reduction in wave height was observed after waves passed over coral reefs. Statistical evaluation indicates that wave height attenuation increases as offshore wave conditions intensify, with an average 50% reduction for higher sea states. Furthermore, regional analysis after extreme events demonstrates decreased wave attenuation in areas with reduced hard coral cover. The study highlights the potential of satellite altimetry in observing wave height changes across coral reefs. Additionally, this study contributes to knowledge of wave behavior in coral reefs, showing the dependency of the attenuation degree on various sea states.